Analysis of the β-Glucosidase Family Reveals Genes Involved in the Lignification of Stone Cells in Chinese White Pear (Pyrus bretschneideri Rehd.) - Wang, Han; Zhang, Yingjie; Feng, Xiaofeng; Peng, Fulei; Mazoor, Muhammad Aamir; Zhang, Yang; Zhao, Yu; Han, WenLong; Lu, Jinjin; Cao, Yunpeng; Cai, Yongping (Frontiers in Plant Science, 2022)
BGLU β-glucosidases in glycoside hydrolase family 1 (GH1) are involved in many processes of plant secondary metabolism. In particular, its de-glycosylation function plays an important role in the transport of lignin monolignols. No comprehensive study of the BGLU family in Chinese pear (Pyrus bretschneideri Rehd.) has been reported yet. In this study, the 50 BGLU family members from Chinese white pear were identified. Three candidate genes, PbBGLU1, PbBGLU15, and PbBGLU16, that may be involved in lignin synthesis were screened by bioinformatics analysis and qRT-PCR. Subcellular localization showed that all three of these candidate genes were expressed in the extracellular region. Then, we analyzed the functions of PbBGLU1 and PbBGLU16. In situ hybridization analysis showed that PbBGLU1 transcripts were not only localized to some pulp cell walls, lignin deposition, and stone cell areas of a pear fruit, but that was also a small amount of enrichment in normal pear flesh cells. PbBGLU16 transcripts were only enriched in lignin deposition and stone cell areas of pear fruit. Enzyme activity analysis revealed that GST-PbBGLU1 and GST-PbBGLU16 had a stronger activity and higher catalytic efficiency for coniferin than syringin. In addition, GST-PbBGLU16 exhibited the higher activity and catalytic efficiency for the two substrates compared with GST-PbBGLU1. The transformation of PbBGLU1 and PbBGLU16 into Arabidopsis identified that the lignin contents of Arabidopsis BGLU-45 mutant, PbBGLU1-RE, and PbBGLU16-RE were not changed than that of wild-type. However, compared with wild-type Arabidopsis, the overexpression of the plant’s lignin increased in varying degrees. The effect of PbBGLU16 on the lignin increment was greater than that of PbBGLU1 in Arabidopsis. In pear fruits, with transient overexpression of PbBGLU1, the contents of lignin and stone cells were significantly higher (0.01 < P < 0.05) than those with empty vector injection pear fruits. After transient expression of PbBGLU16, lignin in pear fruit increased significantly (0.01 < P < 0.05) and stone cells showed a very significant difference (P < 0.01) compared with the control group. However, RNA interference silenced these two genes in pear fruit, which seemed to have no impression on lignin and stone cells. This study provides a molecular biological basis for improving pear fruit quality at the molecular level.